2015
DOI: 10.5001/omj.2015.51
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Nausea and Vomiting: Palonosetron with Dexamethasone vs. Ondansetron with Dexamethasone in Laparoscopic Hysterectomies

Abstract: The combination of palonosetron with dexamethasone is more effective in treating early, delayed, and long term PONV compared to ondansetron with dexamethasone in patients undergoing elective laparoscopic hysterectomies under general anesthesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…Dexamethasone is a common component of the combination therapy, whose antiemetic effect has also been proven by various studies conducted. 12,13,14,15,16,17 So keeping in mind the recently concluded fact that a multimodal management and routine antiemetic prophylaxis results in an increased level of patient's satisfaction than symptomatic treatment in high risk population, which is supported by the numerous studies done on this topic, 18,19,20 we would compare the antiemetic effect of palonosetron (monotherapy) and palonosetron with dexamethasone (combination therapy) in the management of postoperative nausea and vomiting following laparoscopic cholecystectomy under general anaesthesia in our study.…”
mentioning
confidence: 68%
See 1 more Smart Citation
“…Dexamethasone is a common component of the combination therapy, whose antiemetic effect has also been proven by various studies conducted. 12,13,14,15,16,17 So keeping in mind the recently concluded fact that a multimodal management and routine antiemetic prophylaxis results in an increased level of patient's satisfaction than symptomatic treatment in high risk population, which is supported by the numerous studies done on this topic, 18,19,20 we would compare the antiemetic effect of palonosetron (monotherapy) and palonosetron with dexamethasone (combination therapy) in the management of postoperative nausea and vomiting following laparoscopic cholecystectomy under general anaesthesia in our study.…”
mentioning
confidence: 68%
“…There were some debates in relation to the dose of palonosetron 18 and dexamethasone 23 as the prophylaxis of PONV during our study. We considered using the dose of 0.075 mg palonosetron and 8 mg dexamethasone, as it was used most frequently in various previous studies.…”
Section: Grp P (N = 50)mentioning
confidence: 99%
“…However, in most studies comparing the efficacy of palonosetron in preventing PONV with other 5-HT 3 receptor antagonists, including ondansetron, identical drug administration timing was used due to the blinding method. In many cases, preoperative single administration was selected [ 8 – 15 ]. In these studies, most authors reported superior efficacy of palonosetron in preventing PONV compared with ondansetron [ 8 – 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have compared the efficacy of palonosetron to prevent PONV with the older 5-HT 3 receptor antagonists. However, most studies that have compared the efficacy of palonosetron to prevent PONV with ondansetron have used single preoperative drug administration timing and have not considered the relatively short half-life of ondansetron [ 8 – 15 ]. Considering the relatively short half-life of ondansetron, studies utilizing a continuous infusion of ondansetron are rare, and this issue remains controversial.…”
Section: Introductionmentioning
confidence: 99%
“…Postoperative nausea and vomiting (PONV), is reported as the most common distressing complication of laparoscopic surgeries and anesthesia. 1 The various detrimental effects of PONV are including (i) Physical: in which retching and vomiting are fairly violent acts and the major problem associated with vomiting in the postoperative period is aspiration of vomitus, respiratory obstruction and aspiration pneumonia; (ii) Metabolic: which includes anorexia, dehydration and alkalemia; (iii) Psychological: which may cause life-long aversion to surgery as nausea is a very aversive stimulus if induced by operative experience. 2 Over the years, numerous approaches have been used in the management of PONV.…”
Section: Introductionmentioning
confidence: 99%